Bioactive alkaloids in vertically transmitted fungal endophytes. (14th March 2013) - Panaccione, Daniel G.; Beaulieu, Wesley T.; Cook, Daniel; Allen, Edith
Summary Plants form mutualistic symbioses with a variety of microorganisms including endophytic fungi that live inside the plant and cause no overt symptoms of infection. Some endophytic fungi form defensive mutualisms based on the production of bioactive metabolites that protect the plant from herbivores in exchange for a protected niche and nutrition from the host plant. Key elements of these symbioses are vertical transmission of the fungus through seed of the host plant, a narrow host range, and production of bioactive metabolites by the fungus. Grasses frequently form symbioses with endophytic fungi belonging to the family Clavicipitaceae. These symbioses have been studied extensively because of their significant impacts on insect and mammalian herbivores. Many of the impacts are likely due to the production of four classes of bioactive alkaloids – ergot alkaloids, lolines, indole‐diterpenes and peramine – that are distributed in different combinations among endophyte taxa. Several legumes, including locoweeds, are associated with a toxic syndrome called locoism as a result of their accumulation of swainsonine. Species in two genera were recently found to contain previously undescribed endophytic fungi (Undifilum spp., family Pleosporaceae) that are the source of that toxin. The fungi are strictly vertically transmitted and have narrow host ranges. Some plant species in the morning glory family (Convolvulaceae) also form symbioses with endophytic fungi of the Clavicipitaceae that produce ergot alkaloids and, perhaps in at least one case, lolines. Other species in this plant family form symbioses with undescribed fungi that produce swainsonine. The swainsonine‐producing endophytes associated with the Convolvulaceae are distinct from the Undifilum spp. associated with locoweeds and the Clavicipitaceous fungi associated with Convolvulaceae. In the establishment of vertically transmitted symbioses, fungi must have entered the symbiosis with traits that were immediately useful to the plant. Bioactive metabolites are likely candidates for such pre‐adapted traits which were likely useful to the free‐living fungi as well. With future research, vertically transmitted fungi from diverse clades with narrow host ranges and that produce bioactive compounds are likely to be found as important mutualists in additional plants.